Epigenetics-by-sex interaction for somatization conferred by methylation at the promoter region of SLC6A4 gene - Palma-Gudiel, Helena; Deuschle, Michael (Progress in neuro-psychopharmacology & biological psychiatry, 2019)
Background Depression, anxiety and somatoform disorders are all more prevalent in women than in men. However, specific biological mechanisms contributing to such sex differences remain unknown. Serotonergic pathways are involved in mood and behavior regulation and thus have been suggested to be altered in several psychiatric disorders. The serotonin transporter (SERT), encoded by SLC6A4 gene, has received major attention due to its crucial role in serotonergic transmission. Methods 148 monozygotic twin subjects were assessed for (i) lifetime categorical diagnosis of anxious-depressive disorders, following SCID-I-based DSM-IV criteria, and (ii) current psychiatric symptomatology, from a dimensional approach, by means of the Brief Symptom Inventory (BSI). SLC6A4 gene methylation was analyzed by means of Infinium HumanMethylation450 in a subset of the sample. CpG-specific methylation at the promoter region of SLC6A4 gene was further analyzed by means of pyrosequencing technology in the total sample. Results SLC6A4 methylation was found to be significantly higher in women when compared to men independent of DSM-IV diagnosis. SLC6A4 methylation was further associated with the BSI-derived somatization dimension. Conclusions Female hypermethylation of a discrete region located within SLC6A4 promoter region could underlie differential SERT expression in women when compared to men and could be one of the causative mechanisms by which women exhibit increased prevalence of somatic symptoms.
Available online 08 September 2018
Gesehen am 13.02.2019